Recognizing electrocardiographically subtle occlusion myocardial infarction and differentiating it from mimics: Ten steps to or away from cath lab - (:unkn) unknown (AVES, 2021)
It is increasingly evident that the ST-segment elevation (STE) myocardial infarction (MI)/non-STEMI paradigm that equates STEMI with acute coronary occlusion (ACO) is deceptive. This unfortunate paradigm, adhered to by the current guidelines, misses at least one-fourth of the ACOs, and unnecessarily over-triages a similar fraction of the patients to the catheterization laboratory. Accordingly, we have been calling for a new paradigm, the occlusion/nonocclusion MI (OMI/NOMI). Although this new OMI/NOMI paradigm is not limited to an electrocardiogram (ECG), the ECG will remain the cornerstone of this new paradigm because of its speed, repeatability, noninvasive nature, wide availability, and high diagnostic power for OMI. This review provides a step-by-step approach to ECG for the diagnosis of OMI.
Keywords: Acute coronary syndrome; coronary occlusion; electrocardiography; myocardial infarction; percutaneous coronary interventions; ST-SEGMENT ELEVATION; BUNDLE-BRANCH BLOCK; EARLY REPOLARIZATION; UNIVERSAL DEFINITION; DIAGNOSIS; PATTERN; PATIENT; QRS; ARTERY; COMMON